Composite modified nylon 66 fiber and preparation method thereof

By adding modified attapulgite, flame retardant monomer salt solution and nano-silica aqueous dispersion into nylon 66 fiber, and blending it with toughening modification components and UV absorber components, a composite modified nylon 66 fiber with good flame retardancy, toughness and resistance to UV aging is prepared, which solves the problem of insufficient flame retardancy and UV aging resistance of nylon 66 fiber.

CN120683625APending Publication Date: 2025-09-23ZHONGWEI CHEM FIBER CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511062848.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing nylon 66 fiber has deficiencies in flame retardancy, toughness and resistance to UV aging, which limits its application in safety and durability.

Method used

The composite modified nylon 66 fiber is formed by adding modified attapulgite, flame retardant monomer salt solution and nano-silicon dioxide aqueous dispersion into nylon 66 fiber, and melt-blending them with toughening modification components and ultraviolet absorber components.

Benefits of technology

The flame retardancy, toughness and UV aging resistance of nylon 66 fiber have been improved, enhancing its safety in fire situations and outdoor service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a composite modified nylon 66 fiber and a preparation method thereof.Attapulgite, a flame-retardant monomer salt solution and a nano-silica aqueous dispersion are added in the polymerization process of nylon 66 salt for polymerization to generate flame-retardant nylon 66, attapulgite serves as a natural nano-material, the flame-retardant monomer salt solution serves as a flame retardant, and the flame-retardant nylon 66 fiber is prepared. The nylon 66 material has good adsorbability and thermal stability, and attapulgite is added in the polymerization process and can be uniformly dispersed in a nylon 66 matrix, so that the thermal stability of the nylon 66 material is improved; the flame-retardant monomer salt is a product containing phosphorus, nitrogen and other flame-retardant elements generated by reaction of 4-(2-(((2-carboxyl ethyl) (phenyl) phosphoryl) oxygen) ethyoxyl)-4-oxohexanoic acid and hexamethylenediamine, during combustion, the phosphorus element can promote char formation, a compact carbon layer is formed to cover the surface of the material, oxygen and heat transfer is isolated, and the flame-retardant performance of the material is improved. And the nitrogen element can release non-combustible gas in the combustion process to dilute the concentration of the combustible gas, so that the flame-retardant effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a composite modified nylon 66 fiber and a preparation method thereof. Background Art

[0002] As an important synthetic fiber, nylon 66 fiber has been widely used in many fields such as textiles, engineering plastics, automotive industry, aviation materials, etc. due to its excellent properties such as high strength, wear resistance and corrosion resistance.

[0003] However, as various industries continue to increase their requirements for material performance, the limitations of traditional nylon 66 fiber are becoming increasingly prominent. In terms of safety, its flame retardant properties are poor. In emergency situations such as fires, it is easy to burn and spread rapidly, generating large amounts of toxic smoke and heat, which seriously threatens people's lives and property. In terms of durability, when exposed to outdoor environments for a long time, ultraviolet rays will cause the molecular chains of nylon 66 fibers to break and degrade, causing the fiber color to turn yellow and the strength to decrease, shortening the service life of the product. At the same time, in some application scenarios that require high material toughness, traditional nylon 66 fibers are relatively brittle and prone to breakage, limiting their further expansion of application scope. Therefore, how to prepare a nylon 66 fiber that has good flame retardancy, resistance to UV aging and excellent mechanical properties has become an urgent problem to be solved in this field. Summary of the Invention

[0004] Technical problems solved In view of the above-mentioned shortcomings of the prior art, the present invention provides a composite modified nylon 66 fiber and a preparation method thereof, which can effectively solve the problems of poor flame retardancy, toughness and UV aging resistance of nylon 66 fiber in the prior art.

[0005] Technical Solution To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a composite modified nylon 66 fiber, the preparation method comprising: S1. Modifying the purified attapulgite to prepare modified attapulgite: weighing 30-40 g of the modified attapulgite and dispersing it in 1 L of anhydrous ethanol; adding 300-400 g of nylon 66 salt and performing ultrasonic dispersion treatment; the resultant mixture is recorded as nylon 66 salt mixed solution; S2, adding 30-45g of flame retardant monomer salt solution and 10-12g of nano-silicon dioxide aqueous dispersion to the nylon 66 salt mixture, adjusting the pH value to 8-9 with hexamethylenediamine, and then adding 2-3g of hypophosphorous acid. The result is recorded as the reaction system; S3, placing the reaction system in a reactor for reaction treatment to obtain flame-retardant nylon 66; S4. 100 parts by weight of flame-retardant nylon 66, 8-10 parts by weight of a toughening and modifying component, and 1-2 parts by weight of an ultraviolet absorber component are melt-blended, and then spun to obtain a composite modified nylon 66 fiber.

[0006] Furthermore, the purification method in S1 is: S1.1. Dissolve 1-2 g of sodium pyrophosphate in 200 g of deionized water to prepare a dispersant solution. Add 20 g of attapulgite while stirring magnetically at 400-500 rpm. Continue stirring for 1 h, then ultrasonically vibrate at 400 W. The resulting solution is recorded as the dispersed component. S1.2. After the dispersed components were allowed to stand for 4 hours, the upper layer of solution was taken, and centrifuged at a speed of 6000 r / min for 5 minutes. The lower layer of precipitate was placed in an oven at 90°C and dried to constant weight. The purified attapulgite was obtained after grinding through a 200-mesh sieve.

[0007] Furthermore, the preparation method of the modified attapulgite in S1 is: Weigh 2-3 g of purified attapulgite and disperse it in 200 g of anhydrous ethanol. After ultrasonic dispersion at a frequency of 30-40 kHz for 30 minutes, add 0.3-0.5 g of silane coupling agent hydrolyzate dropwise. Stir at a speed of 300-400 r / min for 24 hours, filter and remove the filtrate, and place in an oven at 65°C to dry to constant weight. The result is modified attapulgite.

[0008] Furthermore, the preparation method of the silane coupling agent hydrolyzate is: 3-5g of silane coupling agent KH-550 was hydrolyzed in 100g of deionized water, and stirred at a speed of 400-500r / min for 30min to obtain a silane coupling agent hydrolyzate.

[0009] Furthermore, the flame retardant monomer salt solution in S2 is prepared by: Under a nitrogen atmosphere, 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid and hexamethylenediamine in equal molar ratios were added to deionized water, and the mixture was stirred at 300-500 r / min at a temperature of 60° C. for 1 hour to obtain a solution with a pH value of 7-8. The result was a flame retardant monomer salt solution.

[0010] Furthermore, the reaction processing method in S3 is: S3.1. The reaction system was placed in a reactor and evacuated and filled with nitrogen three times. The temperature was raised to 220-250°C with stirring at 300-400 rpm at an internal pressure of 0.2-0.3 MPa. The reaction was then maintained at constant temperature and pressure for 3 h at an internal pressure of 1.9-2.5 MPa. S3.2. Continue heating to 250-265°C and then reduce the pressure to normal pressure. Then, heat to 270-280°C and react at normal pressure for 30 min. Maintain the temperature and evacuate the reactor to a vacuum of -0.1 MPa. React under vacuum for 10-30 min until the torque reaches 3-4 N·m. Stop stirring and pressurize with nitrogen to discharge the material. S3.3. After cooling, place it in an oven at 60°C and dry it for 24 hours. Then, place it in a vacuum oven at 90°C and dry it for 6 hours. The result is flame retardant nylon 66.

[0011] Furthermore, the preparation method of the toughening and modifying component in S4 is: Weigh 100g of EPDM rubber, 2-3g of maleic anhydride, 0.2-0.3g of dicumyl peroxide and 0.2-0.3g of antioxidant 1010, pour them into 300-350g of acetone, stir at a speed of 200-300r / min for 30min, and then dry at a temperature of 68°C. Then put it into a twin-screw extruder for melt extrusion, and the obtained toughening modification component after granulation is obtained.

[0012] Furthermore, the preparation method of the ultraviolet absorber component in S4 is: Weigh 2-3 parts of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-3 parts of 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 3-5 parts of nano-titanium dioxide, 1-2 parts of nano-zinc oxide and 0.5-0.6 parts of silane coupling agent KH-550 by weight, pour them into a ball mill, and ball mill for 30 minutes at a ball-to-material ratio of 20:1 to obtain the ultraviolet absorber component.

[0013] Furthermore, the temperature of melt blending in S4 is 265-280°C.

[0014] A composite modified nylon 66 fiber is prepared by a preparation method of the composite modified nylon 66 fiber.

[0015] Beneficial effects The present invention provides a composite modified nylon 66 fiber and a preparation method thereof. Compared with the existing known technology, the present invention has the following beneficial effects: 1. The present invention adds attapulgite, a flame retardant monomer salt solution and a nano-silica aqueous dispersion to the polymerization process of nylon 66 salt to generate flame retardant nylon 66. As a natural nanomaterial, attapulgite has good adsorption and thermal stability. When added during the polymerization process, attapulgite can be evenly dispersed in the nylon 66 matrix, thereby improving the thermal stability of the nylon 66 material. The flame retardant monomer salt is a product containing flame retardant elements such as phosphorus and nitrogen generated by the reaction of 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid and hexamethylenediamine. During combustion, the phosphorus element can promote carbonization to form a dense layer. The carbon layer covers the surface of the material, isolating the transfer of oxygen and heat. The nitrogen element will release non-combustible gas during the combustion process, diluting the concentration of combustible gas, thereby achieving a flame retardant effect. The addition of nano-silica aqueous dispersion can further enhance the flame retardant properties. Nano-silica has a large specific surface area and excellent thermal stability. During the combustion process, it can adsorb and fix the free radicals produced by combustion, inhibit the progress of the combustion chain reaction, and at the same time, it can also interweave with the carbon layer generated by the reaction of flame retardant monomer salts, enhance the strength and stability of the carbon layer, and improve the heat insulation and oxygen isolation effects, so that the prepared flame retardant nylon 66 has better thermal stability and flame retardancy.

[0016] 2. The toughening and modifying component in the present invention is based on EPDM rubber and is modified by adding maleic anhydride, dicumyl peroxide and antioxidant 1010. Maleic anhydride can chemically react with EPDM rubber and nylon 66 to form chemical bonds, thereby enhancing the interfacial bonding between the two. Dicumyl peroxide, as a cross-linking agent, can form a cross-linked structure between the molecular chains of EPDM rubber, thereby improving the strength and elasticity of the rubber. Antioxidant 1010 can prevent oxidative degradation of the rubber during processing and use. During the melt blending process, the toughening and modifying component is uniformly dispersed in the flame-retardant nylon 66 matrix. When the material is subjected to external force, the rubber particles can induce silver streaks and shear bands, absorb energy, and thus improve the toughness of the flame-retardant nylon 66.

[0017] 3. The ultraviolet absorber component of the present invention is composed of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, nano-titanium dioxide, nano-zinc oxide and silane coupling agent KH-550. 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole can absorb ultraviolet rays and convert them into harmless heat energy for release, thereby reducing the damage of ultraviolet rays to nylon 66 fibers; nano-titanium dioxide and nano-zinc oxide not only have ultraviolet absorption properties, but also have photocatalytic activity, and can convert the absorbed ultraviolet energy into chemical energy, decompose surrounding organic matter, and further protect the fiber from ultraviolet aging; and the silane coupling agent KH-550 can improve the interface bonding between the nanoparticles and the matrix, enhance the dispersibility and stability of the ultraviolet absorber component in the fiber, and ensure that it can fully exert its anti-ultraviolet aging effect. DETAILED DESCRIPTION

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0019] The present invention will be further described below with reference to the embodiments.

[0020] The sources of some components in the Examples and Comparative Examples are as follows: Attapulgite, Lingshou County Qianhao Mineral Products Processing Plant; Nylon 66 salt, BASF; Silane coupling agent KH-550, Sinopharm Chemical Reagent Co., Ltd.; Sodium pyrophosphate, Guangdong Mingtong Biotechnology Co., Ltd.; Anhydrous ethanol, Sinopharm Chemical Reagent Co., Ltd.; 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid, CPPOA, Chengdu Tuoli Chemical Industry Co., Ltd.; Hexamethylenediamine, Sinopharm Chemical Reagent Co., Ltd.; Nano-silica aqueous dispersion, Shenzhen Jingcai Chemical Co., Ltd.; Hypophosphorous acid, Beijing Hengye Zhongyuan Chemical Co., Ltd.; EPDM rubber, China National Petroleum Corporation Jilin Chemical Industry Group; Maleic anhydride, Jiangsu Longrui Chemical Co., Ltd.; Dicumyl peroxide, Shanghai Reagent Factory No. 1; Antioxidant 1010, Ciba, Switzerland; Acetone, Sinopharm Chemical Reagent Co., Ltd.; 2-(2'-Hydroxy-5'-methylphenyl)benzotriazole, Hubei Jianchu Biopharmaceutical Co., Ltd.; 2-(2'-Hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole, Kehua Wisdom (Shenzhen) Innovative Drug Research and Development Co., Ltd.; Nano-titanium dioxide, Nanjing Baoket New Materials Co., Ltd.; Nano zinc oxide, Fujian Ruisen New Materials Co., Ltd.; Nylon 66 chips, Huafeng Group Co., Ltd.

[0021] Example 1 The preparation method of a composite modified nylon 66 fiber of this embodiment is as follows: S1. Modifying the purified attapulgite to prepare modified attapulgite: 30 g of the modified attapulgite was dispersed in 1 L of anhydrous ethanol, 300 g of nylon 66 salt was added, and then ultrasonic dispersion was performed. The resultant mixture was recorded as nylon 66 salt mixed solution; Among them, the purification method is: S1.1. Dissolve 1 g of sodium pyrophosphate in 200 g of deionized water to prepare a dispersant solution. Add 20 g of attapulgite while stirring magnetically at 400 rpm. Continue stirring for 1 h and then ultrasonically vibrate the solution at 400 W. The resulting solution is referred to as the dispersed fraction. S1.2. After the dispersed components were allowed to stand for 4 hours, the upper layer of solution was taken, and centrifuged at a speed of 6000 r / min for 5 minutes. The lower layer of precipitate was placed in an oven at 90°C and dried to constant weight. The purified attapulgite was obtained after grinding through a 200-mesh sieve.

[0022] The preparation method of modified attapulgite is as follows: 3 g of silane coupling agent KH-550 was hydrolyzed in 100 g of deionized water and stirred at a speed of 400 r / min for 30 min to obtain a silane coupling agent hydrolyzate; 2 g of purified attapulgite was weighed and dispersed in 200 g of anhydrous ethanol. After ultrasonic dispersion at a frequency of 30 kHz for 30 min, 0.3 g of silane coupling agent hydrolyzate was added dropwise. After stirring at a speed of 300 r / min for 24 h, the filtrate was removed by filtration and placed in an oven at 65°C to dry to constant weight. The result was modified attapulgite.

[0023] S2, adding 30g of flame retardant monomer salt solution and 10g of nano-silicon dioxide aqueous dispersion to the nylon 66 salt mixture, adjusting the pH value to 8 with hexamethylenediamine, and then adding 2g of hypophosphorous acid. The result is recorded as the reaction system; Wherein, the preparation method of flame retardant monomer salt solution is: Under a nitrogen atmosphere, 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid and hexamethylenediamine in an equal molar ratio were added to deionized water, and the mixture was stirred at 300 r / min at a temperature of 60° C. for 1 hour to obtain a solution with a pH value of 7. The result was a flame retardant monomer salt solution.

[0024] S3, placing the reaction system in a reactor for reaction treatment to obtain flame-retardant nylon 66; Wherein, the method of reaction treatment is: S3.1. The reaction system was placed in a reactor and evacuated and filled with nitrogen three times. The mixture was heated to 220°C with stirring at 300 r / min at an internal pressure of 0.2 MPa. The reaction was then maintained at a constant temperature and pressure of 1.9 MPa for 3 h. S3.2. Continue heating to 250°C and then reduce the pressure to normal pressure. Then, heat to 270°C and react at normal pressure for 30 min. Maintain the temperature and evacuate the reactor to a vacuum of -0.1 MPa. React under vacuum for 10 min until the torque reaches 3 N·m. Stop stirring and pressurize with nitrogen to discharge the material. S3.3. After cooling, place it in an oven at 60°C and dry it for 24 hours. Then, place it in a vacuum oven at 90°C and dry it for 6 hours. The result is flame retardant nylon 66.

[0025] S4. 100 parts by weight of flame-retardant nylon 66, 8 parts by weight of a toughening modification component and 1 part by weight of an ultraviolet absorber component are melt-blended at a temperature of 265° C., and then spun to obtain a composite modified nylon 66 fiber.

[0026] Wherein, the preparation method of the toughening modification component is: 100 g of EPDM rubber, 2 g of maleic anhydride, 0.2 g of dicumyl peroxide and 0.2 g of antioxidant 1010 were weighed and poured into 300 g of acetone. The mixture was stirred at a speed of 200 r / min for 30 min and then dried at a temperature of 68°C. The mixture was then put into a twin-screw extruder for melt extrusion. The toughening and modification component was obtained after granulation.

[0027] The preparation method of the ultraviolet absorber component is: 2 parts of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2 parts of 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 3 parts of nano-titanium dioxide, 1 part of nano-zinc oxide and 0.5 parts of silane coupling agent KH-550 were weighed and poured into a ball mill. After ball milling for 30 minutes at a ball-to-material ratio of 20:1, the result was the ultraviolet absorber component.

[0028] A composite modified nylon 66 fiber is prepared by a preparation method of the composite modified nylon 66 fiber.

[0029] Example 2 The preparation method of a composite modified nylon 66 fiber of this embodiment is as follows: S1. Modifying the purified attapulgite to prepare modified attapulgite: 40 g of the modified attapulgite was weighed and dispersed in 1 L of anhydrous ethanol; 400 g of nylon 66 salt was added and then subjected to ultrasonic dispersion treatment; the resultant mixture was recorded as nylon 66 salt mixed solution; Among them, the purification method is: S1.1. Dissolve 2 g of sodium pyrophosphate in 200 g of deionized water to prepare a dispersant solution. Add 20 g of attapulgite while stirring magnetically at 500 rpm. Continue stirring for 1 h and then ultrasonically vibrate the solution at 400 W. The resulting solution is referred to as the dispersed fraction. S1.2. After the dispersed components were allowed to stand for 4 hours, the upper layer of solution was taken, and centrifuged at a speed of 6000 r / min for 5 minutes. The lower layer of precipitate was placed in an oven at 90°C and dried to constant weight. The purified attapulgite was obtained after grinding through a 200-mesh sieve.

[0030] The preparation method of modified attapulgite is as follows: 5 g of silane coupling agent KH-550 was hydrolyzed in 100 g of deionized water and stirred at a speed of 500 r / min for 30 min to obtain a silane coupling agent hydrolyzate; 3 g of purified attapulgite was weighed and dispersed in 200 g of anhydrous ethanol. After ultrasonic dispersion at a frequency of 40 kHz for 30 min, 0.5 g of silane coupling agent hydrolyzate was added dropwise. After stirring at a speed of 400 r / min for 24 h, the filtrate was removed by filtration and placed in an oven at 65°C to dry to constant weight. The result was modified attapulgite.

[0031] S2, adding 45g of flame retardant monomer salt solution and 12g of nano-silicon dioxide aqueous dispersion to the nylon 66 salt mixture, adjusting the pH value to 9 with hexamethylenediamine, and then adding 3g of hypophosphorous acid. The result is recorded as the reaction system; Wherein, the preparation method of flame retardant monomer salt solution is: Under a nitrogen atmosphere, 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid and hexamethylenediamine in an equal molar ratio were added to deionized water, and the mixture was stirred at 500 r / min at a temperature of 60°C for 1 hour to obtain a solution with a pH value of 8. The result was a flame retardant monomer salt solution.

[0032] S3, placing the reaction system in a reactor for reaction treatment to obtain flame-retardant nylon 66; Wherein, the method of reaction treatment is: S3.1. The reaction system was placed in a reactor and evacuated and filled with nitrogen three times. The temperature was raised to 250°C with stirring at 400 r / min at an internal pressure of 0.3 MPa. The reaction was then maintained at constant temperature and pressure for 3 h at an internal pressure of 2.5 MPa. S3.2. Continue heating to 265°C and then reduce the pressure to normal pressure. Then, heat to 280°C and react at normal pressure for 30 min. Maintain the temperature and evacuate the reactor to a vacuum of -0.1 MPa. React under vacuum for 30 min until the torque reaches 4 N·m. Stop stirring and pressurize with nitrogen to discharge the material. S3.3. After cooling, place it in an oven at 60°C and dry it for 24 hours. Then, place it in a vacuum oven at 90°C and dry it for 6 hours. The result is flame retardant nylon 66.

[0033] S4. 100 parts by weight of flame-retardant nylon 66, 10 parts by weight of a toughening modification component and 2 parts by weight of an ultraviolet absorber component are melt-blended at a temperature of 280° C., and then spun to obtain a composite modified nylon 66 fiber.

[0034] Wherein, the preparation method of the toughening modification component is: 100 g of EPDM rubber, 3 g of maleic anhydride, 0.3 g of dicumyl peroxide and 0.3 g of antioxidant 1010 were weighed and poured into 350 g of acetone. The mixture was stirred at a speed of 300 r / min for 30 min and then dried at a temperature of 68°C. The mixture was then put into a twin-screw extruder for melt extrusion. The toughening and modification component was obtained after granulation.

[0035] The preparation method of the ultraviolet absorber component is: 3 parts of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3 parts of 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 5 parts of nano-titanium dioxide, 2 parts of nano-zinc oxide and 0.6 parts of silane coupling agent KH-550 were weighed and poured into a ball mill. After ball milling for 30 minutes at a ball-to-material ratio of 20:1, the result was the ultraviolet absorber component.

[0036] A composite modified nylon 66 fiber is prepared by a preparation method of the composite modified nylon 66 fiber.

[0037] Example 3 The preparation method of a composite modified nylon 66 fiber of this embodiment is as follows: S1. Modifying the purified attapulgite to prepare modified attapulgite: 35 g of the modified attapulgite was dispersed in 1 L of anhydrous ethanol, 400 g of nylon 66 salt was added, and then ultrasonic dispersion was performed. The resultant mixture was recorded as nylon 66 salt mixed solution; Among them, the purification method is: S1.1. Dissolve 2 g of sodium pyrophosphate in 200 g of deionized water to prepare a dispersant solution. Add 20 g of attapulgite while stirring magnetically at 500 rpm. Continue stirring for 1 h and then ultrasonically vibrate the solution at 400 W. The resulting solution is referred to as the dispersed fraction. S1.2. After the dispersed components were allowed to stand for 4 hours, the upper layer of solution was taken, and centrifuged at a speed of 6000 r / min for 5 minutes. The lower layer of precipitate was placed in an oven at 90°C and dried to constant weight. The purified attapulgite was obtained after grinding through a 200-mesh sieve.

[0038] The preparation method of modified attapulgite is as follows: 4 g of silane coupling agent KH-550 was hydrolyzed in 100 g of deionized water and stirred at a speed of 500 r / min for 30 min to obtain a silane coupling agent hydrolyzate; 3 g of purified attapulgite was weighed and dispersed in 200 g of anhydrous ethanol. After ultrasonic dispersion at a frequency of 35 kHz for 30 min, 0.4 g of silane coupling agent hydrolyzate was added dropwise. The mixture was stirred at a speed of 400 r / min for 24 h, and then the filtrate was removed by filtration. The mixture was placed in an oven at 65°C and dried to constant weight to obtain modified attapulgite.

[0039] S2, adding 38g of flame retardant monomer salt solution and 11g of nano-silicon dioxide aqueous dispersion to the nylon 66 salt mixture, adjusting the pH value to 9 with hexamethylenediamine, and then adding 3g of hypophosphorous acid. The result is recorded as the reaction system; Wherein, the preparation method of flame retardant monomer salt solution is: Under a nitrogen atmosphere, 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid and hexamethylenediamine in an equal molar ratio were added to deionized water, and the mixture was stirred at 400 r / min at a temperature of 60° C. for 1 hour to obtain a solution with a pH value of 8. The result was a flame retardant monomer salt solution.

[0040] S3, placing the reaction system in a reactor for reaction treatment to obtain flame-retardant nylon 66; Wherein, the method of reaction treatment is: S3.1. The reaction system was placed in a reactor and evacuated and filled with nitrogen three times. The temperature was raised to 240°C with stirring at 400 r / min at an internal pressure of 0.3 MPa. The reaction was then maintained at constant temperature and pressure for 3 h at an internal pressure of 2.2 MPa. S3.2. Continue heating to 258°C and then reduce the pressure to normal pressure. Then, heat to 275°C and react at normal pressure for 30 min. Maintain the temperature and evacuate the reactor to a vacuum of -0.1 MPa. React under vacuum for 20 min until the torque reaches 4 N·m. Stop stirring and pressurize with nitrogen to discharge the material. S3.3. After cooling, place it in an oven at 60°C and dry it for 24 hours. Then, place it in a vacuum oven at 90°C and dry it for 6 hours. The result is flame retardant nylon 66.

[0041] S4. 100 parts by weight of flame-retardant nylon 66, 9 parts by weight of a toughening modification component and 2 parts by weight of an ultraviolet absorber component are melt-blended at a temperature of 275° C., and then spun to obtain a composite modified nylon 66 fiber.

[0042] Wherein, the preparation method of the toughening modification component is: 100 g of EPDM rubber, 3 g of maleic anhydride, 0.3 g of dicumyl peroxide and 0.3 g of antioxidant 1010 were weighed and poured into 330 g of acetone. The mixture was stirred at a speed of 300 r / min for 30 min and then dried at a temperature of 68°C. The mixture was then put into a twin-screw extruder for melt extrusion. The toughening and modification component was obtained after granulation.

[0043] The preparation method of the ultraviolet absorber component is: 2 parts of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3 parts of 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 4 parts of nano-titanium dioxide, 2 parts of nano-zinc oxide and 0.6 parts of silane coupling agent KH-550 were weighed and poured into a ball mill. After ball milling for 30 minutes at a ball-to-material ratio of 20:1, the result was the ultraviolet absorber component.

[0044] A composite modified nylon 66 fiber is prepared by a preparation method of the composite modified nylon 66 fiber.

[0045] Comparative Example 1 The preparation method of a composite modified nylon 66 fiber provided in this comparative example is substantially the same as that in Example 1, with the main difference being that the flame-retardant nylon 66 in Example 1 is replaced with nylon 66 chips in this comparative example.

[0046] Comparative Example 2 The preparation method of a composite modified nylon 66 fiber provided in this comparative example is substantially the same as that in Example 1, with the main difference being that the toughening and modifying component in Example 1 is replaced with EPDM rubber in this comparative example.

[0047] Comparative Example 3 The preparation method of a composite modified nylon 66 fiber provided in this comparative example is substantially the same as that in Example 1, with the main difference being that the ultraviolet absorber component in Example 1 is replaced with 2-(2'-hydroxy-5'-methylphenyl)benzotriazole in this comparative example.

[0048] Performance Testing The composite modified nylon 66 fibers prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. The properties of Examples 1-3 and Comparative Examples 1-3 were tested. The specific testing methods and test items are as follows: 1. The limiting oxygen index of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T2406.2-2009, and the obtained data were recorded in the following table; 2. The tensile strength of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T1040.2-2006, and the obtained data were recorded in the following table; 3. The notched impact strength of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T1843-2008, and the obtained data are recorded in the following table; 4. Examples 1-3 and Comparative Examples 1-3 were irradiated under ultraviolet radiation with a wavelength of 365 nm for 240 h, and the surface changes of Examples 1-3 and Comparative Examples 1-3 were recorded. The obtained data are recorded in the following table; Limiting oxygen index tensile strength Notched impact strength Surface changes Example 1 27.9 70.98 82.34 No significant changes Example 2 28.1 69.46 80.65 No significant changes Example 3 27.6 68.97 81.27 No significant changes Comparative Example 1 20.6 58.35 62.97 No significant changes Comparative Example 2 27.3 59.74 65.38 No significant changes Comparative Example 3 27.1 68.64 79.48 Surface turns yellow The data in the above table show that the flame retardant properties, mechanical properties and anti-ultraviolet aging properties of the composite modified nylon 66 fibers in Examples 1-3 are significantly better than those in Comparative Examples 1-3, indicating that using flame-retardant nylon 66 as the base material in the preparation of the composite modified nylon 66 fibers can improve their flame retardant properties, the addition of the toughening modification component can significantly improve the toughness of the composite modified nylon 66 fibers, and the addition of the composite ultraviolet absorber component can significantly improve the anti-ultraviolet aging properties of the composite modified nylon 66 fibers.

[0049] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply the existence of any such actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article, or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or device. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of other identical elements in the process, method, article, or device comprising the element.

[0050] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A method for preparing a composite modified nylon 66 fiber, characterized in that: The preparation method is: S1. Modifying the purified attapulgite to prepare modified attapulgite: weighing 30-40 g of the modified attapulgite and dispersing it in 1 L of anhydrous ethanol; adding 300-400 g of nylon 66 salt and performing ultrasonic dispersion treatment; the resultant mixture is recorded as nylon 66 salt mixed solution; S2, adding 30-45g of flame retardant monomer salt solution and 10-12g of nano-silicon dioxide aqueous dispersion to the nylon 66 salt mixture, adjusting the pH value to 8-9 with hexamethylenediamine, and then adding 2-3g of hypophosphorous acid. The result is recorded as the reaction system; S3, placing the reaction system in a reactor for reaction treatment to obtain flame-retardant nylon 66; S4. 100 parts by weight of flame-retardant nylon 66, 8-10 parts by weight of a toughening and modifying component, and 1-2 parts by weight of an ultraviolet absorber component are melt-blended, and then spun to obtain a composite modified nylon 66 fiber.

2. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The purification method in S1 is: S1.

1. Dissolve 1-2 g of sodium pyrophosphate in 200 g of deionized water to prepare a dispersant solution. Add 20 g of attapulgite while stirring magnetically at 400-500 rpm. Continue stirring for 1 h, then ultrasonically vibrate at 400 W. The resulting solution is recorded as the dispersed component. S1.

2. After the dispersed components were allowed to stand for 4 hours, the upper layer of solution was taken, and centrifuged at a speed of 6000 r / min for 5 minutes. The lower layer of precipitate was placed in an oven at 90°C and dried to constant weight. The purified attapulgite was obtained after grinding through a 200-mesh sieve.

3. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The preparation method of the modified attapulgite in S1 is: Weigh 2-3 g of purified attapulgite and disperse it in 200 g of anhydrous ethanol. After ultrasonic dispersion at a frequency of 30-40 kHz for 30 minutes, add 0.3-0.5 g of silane coupling agent hydrolyzate dropwise. Stir at a speed of 300-400 r / min for 24 hours, filter and remove the filtrate, and place in an oven at 65°C to dry to constant weight. The result is modified attapulgite.

4. The method for preparing a composite modified nylon 66 fiber according to claim 3, characterized in that: The preparation method of the silane coupling agent hydrolyzate is: 3-5g of silane coupling agent KH-550 was hydrolyzed in 100g of deionized water, and stirred at a speed of 400-500r / min for 30min to obtain a silane coupling agent hydrolyzate.

5. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The preparation method of the flame retardant monomer salt solution in S2 is: Under a nitrogen atmosphere, 4-(2-(((2-carboxyethyl)(phenyl)phosphoryl)oxy)ethoxy)-4-oxohexanoic acid and hexamethylenediamine in equal molar ratios were added to deionized water, and the mixture was stirred at 300-500 r / min at a temperature of 60° C. for 1 hour to obtain a solution with a pH value of 7-8. The result was a flame retardant monomer salt solution.

6. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The reaction processing method in S3 is: S3.

1. The reaction system was placed in a reactor and evacuated and filled with nitrogen three times. The temperature was raised to 220-250°C with stirring at 300-400 rpm at an internal pressure of 0.2-0.3 MPa. The reaction was then maintained at constant temperature and pressure for 3 h at an internal pressure of 1.9-2.5 MPa. S3.

2. Continue heating to 250-265°C and then reduce the pressure to normal pressure. Then, heat to 270-280°C and react at normal pressure for 30 min. Maintain the temperature and evacuate the reactor to a vacuum of -0.1 MPa. React under vacuum for 10-30 min until the torque reaches 3-4 N·m. Stop stirring and pressurize with nitrogen to discharge the material. S3.

3. After cooling, place it in an oven at 60°C and dry it for 24 hours. Then, place it in a vacuum oven at 90°C and dry it for 6 hours. The result is flame retardant nylon 66.

7. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The preparation method of the toughening modification component in S4 is: Weigh 100g of EPDM rubber, 2-3g of maleic anhydride, 0.2-0.3g of dicumyl peroxide and 0.2-0.3g of antioxidant 1010, pour them into 300-350g of acetone, stir at a speed of 200-300r / min for 30min, and then dry at a temperature of 68°C. Then put it into a twin-screw extruder for melt extrusion, and the obtained toughening modification component after granulation is obtained.

8. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The preparation method of the ultraviolet absorber component in S4 is: Weigh 2-3 parts of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-3 parts of 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 3-5 parts of nano-titanium dioxide, 1-2 parts of nano-zinc oxide and 0.5-0.6 parts of silane coupling agent KH-550 by weight, pour them into a ball mill, and ball mill for 30 minutes at a ball-to-material ratio of 20:1 to obtain the ultraviolet absorber component.

9. The method for preparing a composite modified nylon 66 fiber according to claim 1, characterized in that: The temperature of melt blending in S4 is 265-280°C.

10. A composite modified nylon 66 fiber, characterized in that: The composite modified nylon 66 fiber is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Halogen-free flame-retardant long glass fiber reinforced nylon 6 material and preparation method thereof

    CN102504529A

  • Preparation method of nylon 66 / attapulgite clay nano-composite fiber

    CN103614804A

  • Preparation method of toughened and anti-static high-performance enhanced polyamide yarns

    CN104357942A

  • In-situ-polymerized halogen-free flame-retardant nylon 6 / attapulgite nano composite material and preparation method thereof

    CN104448299A

  • High-speed spinning polyamide-6 granula and preparation method thereof

    CN108754663A